2011
DOI: 10.1007/978-1-4614-1195-6_3
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Cognitive and Neurobiological Model of Motivated Forgetting

Abstract: Historically, research on forgetting has been dominated by the assumption that forgetting is passive, refl ecting decay, interference, and changes in context. This emphasis arises from the pervasive assumption that forgetting is a negative outcome. Here, we present a functional view of forgetting in which the fate of experience in memory is determined as much by motivational forces that dictate the focus of attention as it is by passive factors. A central tool of motivated forgetting is retrieval suppression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
158
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(174 citation statements)
references
References 163 publications
(215 reference statements)
13
158
1
2
Order By: Relevance
“…The generalized memory impairment by voluntary inhibition suggests the feasibility of interrupting daily life memories, which are linked with various contextual cues. An increasing amount of attention has been directed toward research on intentional inhibition and its potential relevance in understanding and treating clinical disorders (e.g., Anderson, Reinholz, Kuhl, & Mayr, 2011;Joormann et al, 2009;Kupper, Benoit, Dalgleish, & Anderson, 2014;van Schie et al, 2013; for a review see Anderson & Huddleston, 2012). Future attempts should determine whether intentional inhibition is also effective for remote memories.…”
Section: Discussionmentioning
confidence: 97%
“…The generalized memory impairment by voluntary inhibition suggests the feasibility of interrupting daily life memories, which are linked with various contextual cues. An increasing amount of attention has been directed toward research on intentional inhibition and its potential relevance in understanding and treating clinical disorders (e.g., Anderson, Reinholz, Kuhl, & Mayr, 2011;Joormann et al, 2009;Kupper, Benoit, Dalgleish, & Anderson, 2014;van Schie et al, 2013; for a review see Anderson & Huddleston, 2012). Future attempts should determine whether intentional inhibition is also effective for remote memories.…”
Section: Discussionmentioning
confidence: 97%
“…After participants completed this "same-probe" memory task, they also completed an incidental memory test for the target word (Independent-Probe test), in which they were given a category cue and the first letter of the target word (e.g., Tree-P___). This "independent-probe task" has been used previously to test whether the memory for the right-hand members of the word pairs is more difficult to access after repeated attempts to block their retrieval (Anderson and Green, 2001). However, we have shown that children have more difficulty than adults when attempting to retrieve the target word with a probe that differs from that used during initial learning and during the TNT phase (Paz-Alonso et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…To study the neural basis of age-related changes and individual differences in mnemonic control, we adapted the original Think/No-Think (TNT) paradigm (Anderson and Green, 2001;Anderson et al, 2004), modifying the task design and word stimuli in the Bunge laboratory for use with children (Paz-Alonso et al, 2009). The TNT paradigm includes three phases: (1) an initial study phase, during which participants learn a set of word-word associations; (2) the TNT phase, during which they are shown one of the words and asked either to retrieve the associated word (Think trials) or to prevent the associated word from coming to mind (No-Think trials); and (3) the memory test phase, during which participants' memory for all the word pairs is assessed.…”
Section: Overview Of Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Although often thought of as a passive process, people may deliberately and selectively fail to rehearse negative information and therefore forget it over time (Bénabou and Tirole 2002). Motivated forgetting may help people deal with unpleasant life experiences (Anderson and Huddleston 2012) or reduce cognitive dissonance (Akerlof and Dickens 1982). Shu and Gino (2012) conducted four laboratory experiments in which participants completed an ability-based task and were paid according to their performance.…”
Section: Forgettingmentioning
confidence: 99%